2019
DOI: 10.1017/s0954579419000865
|View full text |Cite
|
Sign up to set email alerts
|

The temporal sequence of depressive symptoms, peer victimization, and self-esteem across adolescence: Evidence for an integrated self-perception driven model

Abstract: Depression is associated with a multiplicity of adverse outcomes in adolescence, including peer victimization and low self-esteem. Depressive symptoms, peer victimization, and self-esteem are linked in cross-sectional studies, but no longitudinal study has been conducted assessing their developmental pathways in one integrated model across adolescence. We explored their temporal sequencing in a normative sample of 612 Canadian adolescents (54% girls) assessed annually over 5 years (Grade 7 to Grade 11). Potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 65 publications
0
19
1
1
Order By: Relevance
“…Firstly, those who are bullied are more likely to be less motivated [21] and have lower aspiration [31] to engage in a particular goal such as academic success and achievement. Secondly, victims may have a negative view of themselves [19], have low self-efficacy (the belief in one′s ability to succeed in specific situations or accomplish a task) [23,69] and have low self-concept [24] that can in turn affect their scholastic achievement [36]. Thirdly, victimisation may lead to isolation, school adjustment problems including loneliness, and school avoidance [41] and as a result their self-esteem and their self-efficacy are also affected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, those who are bullied are more likely to be less motivated [21] and have lower aspiration [31] to engage in a particular goal such as academic success and achievement. Secondly, victims may have a negative view of themselves [19], have low self-efficacy (the belief in one′s ability to succeed in specific situations or accomplish a task) [23,69] and have low self-concept [24] that can in turn affect their scholastic achievement [36]. Thirdly, victimisation may lead to isolation, school adjustment problems including loneliness, and school avoidance [41] and as a result their self-esteem and their self-efficacy are also affected.…”
Section: Discussionmentioning
confidence: 99%
“…As well as being repeatedly associated with poor academic achievement (e.g., [8,15,16]), bullying victimisation has been associated with low self-esteem [17][18][19][20], low educational motivation [21], reduced academic self-concept (reading and mathematics) and lower commitment to study, and higher extrinsic motivation and test anxiety rates [22]. Some studies also found a negative association between peer victimisation and academic self-efficacy [23] and self-concept [24].…”
Section: Introductionmentioning
confidence: 99%
“…The interpersonal-scar model proposes the opposite direction of causality: that psychopathology impairs social relationships (i.e., peer difficulties as a lagging indicator). Recent evidence supports this direction of causality (Crawford & Manassis, 2011; Kochel, Ladd, & Rudolph, 2012; Marsh et al, 2016; Rudolph, Ladd, & Dinella, 2007; Saint-Georges & Vaillancourt, 2020; Tran, Cole, & Weiss, 2012; Vaillancourt, Brittain, McDougall, & Duku, 2013). Such models have tended to focus on the relationship between peer victimization and depression, although one study showed that in 5- to 6-year-old children, teacher-reported broad behavior problems (e.g., withdrawal, aggression, depressed/anxious behaviors) predicted increased peer-reported victimization 3 years later (Schwartz et al, 1999).…”
Section: Theoretical Models Of Peer Relations and Psychopathologymentioning
confidence: 87%
“…These theories purport that psychopathology impairs youths’ social skills and abilities to initiate and maintain interpersonal relationships (Hoza, 2007; Nijmeijer et al, 2008; Rudolph, 2009). Yet another theory purports a self-perception-driven model whereby depression mediates the relationship between self-esteem and peer victimization (Saint-Georges & Vaillancourt, 2020). Along with anxiety disorders, others have suggested that behavioral manifestations of social anxiety and depression could make children a target for victimization (Hodges & Perry, 1999; Marsh et al, 2016; Olweus, 1993).…”
Section: Theoretical Models Of Peer Relations and Psychopathologymentioning
confidence: 99%
“…Racial centrality is the degree to which an individual emphasizes that being Black is a key aspect of their self-concept, and private regard is the positive or negative attitudes that a person holds about being Black and other Black people (Sellers et al 1998). Black youth who report higher racial centrality and private regard generally experience less stress and fewer depressive symptoms than Black youth with less race-central attitudes or those who feel negatively about Black people (Sellers et al 2006;Neblett et al 2012;Rivas-Drake et al 2014b).…”
Section: Reducing Risk Via Racial Identitymentioning
confidence: 99%